The contextual integration and sustainable development of Kuala Lumpur’s City Centre waterfront: an evaluation of the policies, law and guidelines - ., Nurul Syala Abdul Latip, Tim Heath, Shuhana Shamsuddin, M. S. Li (2011)
he contextual integration between the water bodies, waterfront and the city has long been established in history when water used to be the main transportation mode. The importance of the integration of water bodies to many cities is globally acknowledged. Over the years, many of these cities have lost their integration with their water bodies due to many factors such as the industrial revolution, development in transportation system and technology. In an attempt to achieve sustainable development, most cities have attempted to reintegrate the city with the water body even to the extent of removing highways which had been constructed parallel to the water body. These expensive approaches are some of the many efforts done due to the increasing awareness on the benefits gained through waterfront regeneration. This has, however, helped to secure the sense of place as well as increasing the quality of living and working environment of the urban community. The lost of integration between the city and the water bodies is also experienced by the capital city of Malaysia, Kuala Lumpur. In the case of Kuala Lumpur city, the Klang and Gombak Rivers that run through the city centre act as the main water bodies. It used to be the life lines of the City when it was the main transportation mode for the people. It was from the rivers and the waterfront area that the morphological development of the city evolves. There are also attempts to reintegrate the rivers to the city since 1979. Based on a qualitative method, this paper employs content analysis and focus interview as the research tools to evaluate existing policies and guidelines available on the contextual integration between the waterfront and the urban river. This paper provides the six main findings which directly contributed to the existing contextual integration between the waterfront and the water bodies. These are i)absence of policy and guidelines before the third morphological period ii) existing policies and guidelines are general and mostly referring to zones rather than according to plots iii) Policy and guideline developed and implemented in isolation by different government agencies iv) lack of guidelines which is suitable to the Kuala Lumpur waterfront. v) lack of detail master planning for Kuala Lumpur waterfront vi) guidelines which are not legally bounded are making implementation difficult. These aspects are important to be underlined so that they are clearly identified, acknowledged and overcome for a more sustainable development of the waterfront in the city centre of Kuala Lumpur.